A peptide mimetic of calcium. - Dillon, J (1991)
Proteins of the troponin superfamily use homologous amino acid sequences as binding sites for Ca2+ and seem to have evolved from an ancestral Ca2+ binding site. We have utilized this ancestral sequence to construct a peptide (Ca(2+)-like peptide) with inverted hydropathy to the calcium-coordinating region of this protein. This synthetic peptide acted like Ca2+ in that (i) it increased the calmodulin-dependent hydrolysis of cAMP by phosphodiesterase, (ii) it interacted with EDTA, and (iii) it enhanced contraction of urinary bladder smooth muscle in vitro. Unlike Ca2+, the peptide's effects were destroyed by acid hydrolysis. These findings demonstrate the synthesis of a peptide that can substitute for Ca2+ and may have considerable utility for the study of Ca(2+)-regulated pathways and possible therapeutic value as a pharmacologic agent.